2011
DOI: 10.1590/s0100-29452011000200036
|View full text |Cite
|
Sign up to set email alerts
|

Potassium fertilization for pineapple: effects on soil chemical properties and plant nutrition

Abstract: -A field experiment was carried out on an Ultisol located at the city of Agudos (22º30'S; 49º03'W), in the state of São Paulo, Brazil, in order to determine the effects of rates and sources of potassium fertilizer on nutritional status of 'Smooth Cayenne' pineapple and on some soil chemical properties. The experiment was a complete factorial design with four rates (0, 175, 350, and 700 kg ha -1 of K 2 O) and three combinations of K sources (100% KCl, 100% K 2 SO 4 and 40% K 2 SO 4 + 60% KCl). Soil samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 4 publications
3
9
0
2
Order By: Relevance
“…Potassium was the nutrient required in greatest quantities by the pineapple plant, which was in agreement with Teixeira et al (2011). Maximum accumulation of K in the plant was 1,404.25 kg ha -1 and occurred at 775 DAP, and the greatest demand for K, expressed by the greater rates of maximum accumulation in the plant and its components of leaves, stem, and roots, occurred from 550 to 775 DAP (Table 1), indicating, as for N, that the greatest demand for K by the pineapple plant occurs in the period before induced flowering, with greater rates of K being recommended in that period.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Potassium was the nutrient required in greatest quantities by the pineapple plant, which was in agreement with Teixeira et al (2011). Maximum accumulation of K in the plant was 1,404.25 kg ha -1 and occurred at 775 DAP, and the greatest demand for K, expressed by the greater rates of maximum accumulation in the plant and its components of leaves, stem, and roots, occurred from 550 to 775 DAP (Table 1), indicating, as for N, that the greatest demand for K by the pineapple plant occurs in the period before induced flowering, with greater rates of K being recommended in that period.…”
Section: Resultssupporting
confidence: 82%
“…At the end of the 'Vitória' pineapple plant crop cycle to obtain mean yield of 72 t ha -1 of fruit, the following decreasing order of total accumulation of macronutrients was observed: 898 kg ha -1 of K, 452 kg ha -1 of N, 134 kg ha -1 of S, 129 kg ha -1 of Ca, 126 kg ha -1 of Mg, and 107 kg ha -1 of P, indicating greater N and K demand by the crop in comparison to other macronutrients, as indicated by Teixeira et al (2011). The 'Vitória' pineapple plant expressed intermediate capacity for taking up macronutrients in comparison to other studies undertaken with the cultivars Pérola and Smooth Cayenne, which showed mean accumulation ranging from 509-1,234 kg ha -1 of K, 238-450 kg ha -1 of N, 161-253 kg ha -1 of Ca, 33-157 kg ha -1 of Mg, 13-75 kg ha -1 of P, and 17-40 kg ha -1 of S (Hiroce et al, 1977;Py et al, 1987).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…There have been many studies on the applications of various organic fertilizer onto pineapple plants, such as using composted poultry manure [17], composted pineapple residue return [18], and other composted materials [19][20][21][22]. According to Darnaudery, et al [23], 'Queen Victoria' pineapple fruits produced via organic fertilization produced the highest total soluble solids content (TSS) and lowest titratable acidity (TA) compared to inorganic fertilization.…”
Section: Introductionmentioning
confidence: 99%
“…Características nutricionais da planta, estimadas por meio de teores foliares de nutrientes na folha D interferem diretamente na produção de frutos, pois a produtividade do abacaxizeiro está vinculada ao estado nutricional da planta (COELHO et al 2007;FEITOSA et al, 2011;SPIRONELLO et al, 2004;TEIXEIRA et al, 2011). Segundo Silva e Lima Jr. (2010) para obtenção de 1,8 kg de massa média de fruto, é preciso que o conteúdo de N, presente na folha "D", no momento da indução floral esteja em 100 mg folha -1 , aproximadamente.…”
Section: Introductionunclassified